THE ROLE OF SERVICE QUALITY ON PERFORMANCE - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The South Sudan banking has seen momentous changes in the post-independence era. It has witnessed introduction of a remarkable shift in its operating environment during the last decade. Various reform measures, both qualitative and quantitative, were introduced with an objective to revitalize Indian banking sector and to meet the future challenges(Carlson, 2010). Every aspect of the functioning of the South Sudan banking industry, be it a customer service, resource mobilization, credit management, asset-liability management, investments, human resource development, and forex management are undergoing dramatic changes with the reforms gathering the momentum and speed. Several innovative IT-based services such as Automated Teller Machines (ATMs), electronic fund transfer (EFT), anywhere-anytime banking, internet banking etc. are being introduced in the South Sudan banking customers(Kassim & Abdullah, 2010).